The Impact of Tax Revenue on Economic Growth in Turkey from 2010 to 2020 - Hussein, Araz Waleed; Mohammud, Harman Salih (Journal of Danubian Studies and Research, 2022)
This study aimed to examine and analyze the impact of tax revenue on economic growth and the relationship between tax revenue and economic growth in Turkey for the period 2010 to 2020. This study purposed that tax revenue has a positive impact on economic growth and has a long-run relationship between variables. According to the ARDL model, results are significant at 5% that accept the null hypothesis and reject the alternative hypothesis which means tax revenue has a positive impact on economic growth. The tax revenue and economic growth have a long-run relationship by the bound test for the study period from 2010 to 2020 in Turkey’s economy.